DEVELOPMENT OF NEW MEDIUM TERMED ECOL FOR DETECTION OF ESCHERICHIA COLI - M.K. Sharifi-Yazdi;C. Azimi (Tehran University of Medical Sciences, 1998)
A new medium, termed Ecol was developed for the detection and enumeration of E. coli. The selective properties of Ecol medium for the detection of E.coli from mixed culture in wastewater was tested and compared with conventional coliform media at 37°C and 44°C. Results clearly showed that ECOL medium was enable to direct confirmation of E.coli to be carried out by the indole reaction. The results indicated that this was an excellent single step medium for E.coli enumeration by the most probable number procedure.